APLIKASI POC DAUN KETAPANG DAN NPK PHONSKA TERHADAP PEMBIBITAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE-NURSERY - Wahyu Eko Saputra; Maizar (UIR Press, 2024)
This study aims to assess the primary interactive effects of POC ketapang leaves and NPK phonska on the growth of oil palm seedlings (Elaeis guineensis Jacq.) during the pre-nursery stage. The research was conducted at the Experimental Farm of the Faculty of Agriculture, Riau Islamic University, located at Jalan Kaharuddin Nasution Km 11 No. 113, Air Winter Village, Bukit Raya District, Pekanbaru City. The duration of the study spanned four months, from September to December 2023. A Completely Randomized Design (CRD) with two factors was employed in this research. The first factor, the application of POC ketapang leaves, included four treatment levels: 0, 25, 50, and 75 ml per liter of water. The second factor, the dosage of NPK phonska, also included four levels: 0, 14, 28, and 42 g per polybag, resulting in 16 treatment combinations, each replicated three times. The parameters measured included plant height, number of leaf sheaths, sheath length, stem diameter, root volume, fresh plant weight, and dry plant weight. Statistical analysis of the data was performed, followed by a Honestly Significant Difference (HSD) test at a 5% significance level. The findings indicate that the interaction between POC ketapang leaf application and NPK phonska significantly influenced plant height, stem diameter, root volume, fresh weight, and dry weight of the plants. However, there were no significant differences observed in the number and length of fronds when considering the interaction. The application of POC ketapang leaves had a significant effect on all measured parameters, with the optimal treatment being 75 ml per liter of water. Similarly, the application of NPK phonska fertilizer significantly impacted all observed parameters, with the most effective treatment being 42 g per polybag.